Comparing cranial biomechanics between Barbourofelis fricki and Smilodon fatalis: Is there a universal killing-bite among saber-toothed predators? - Figueirido-Castillo, Francisco Borja; Tucker, Shane; Lautenschlager, Stephan (Wiley, 2024)
Saber-tooths, extinct apex predators with long and blade-like upper canines, have appeared iteratively at least five times in the evolutionary history of verte brates. Although saber-tooths exhibit a relatively diverse range of morphol ogies, it is widely accepted that all killed their prey using the same predatory behavior. In this study, we CT-scanned the skull of Barbourofelis fricki and compared its cranial mechanics using finite element analysis (FEA) with that of Smilodon fatalis. Our aim was to investigate potential variations in killing behavior between two dirk-toothed sabretooths from the Miocene and Pleisto cene of North America. The study revealed that B. fricki had a stoutly-built skull capable of withstanding stress in various prey-killing scenarios, while the skull of S. fatalis appeared less optimized for supporting stress, which high lights the highly derived saber-tooth morphology of the former. The results may indicate that B. fricki was more of a generalist in prey-killing compared to S. fatalis, which experiences lower stresses under stabbing loads. We hypothe size that morphological specialization in saber-tooths does not necessarily indi cate ecological specialization. Our results support the notion that morphological convergence among saber-toothed cats may obscure differences in hunting strategies employed to dispatch their prey. Our findings challenge the assumption of the universally assumed canine-shear biting as the prey killing behavior of all saber-toothed cats. However, further research involving a wider range of dirk and scimitar-toothed forms could provide additional insights into the diversity of cranial biomechanics within this fascinating group of extinct mammalian predators.
Keywords: Craneo; Vertebrados - Evolución; Barbourofelis; Finite element analysis; Predatory behavior; Skull; Smilodon